2014
DOI: 10.37040/geografie2014119030259
|View full text |Cite
|
Sign up to set email alerts
|

Regional Awareness and Regional Identity in Czechia: Case Study of the Bohemian Paradise

Abstract: Since 1980s, we can observe a changing paradigm within the approaches towards regions which understand and deconstruct the “region” as a social process. Instead of understanding the region as an object or a category, this change transforms the region into a subject of interest for scholars. The study of regions is from now on considered a research topic which requires a holistic understanding of geography, broad interdisciplinary approaches as well as local and historical sensitivity. The paper is using a conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The results further illustrate the fact that the rate of population's feeling of belonging to a region offers the potential for forming a vision for development. This vision should reflect regional specificities, including geographically differentiated relationship to the countryside where people live (Chromý, Semian, Kučera 2014;Walker, Ryan 2008;Lokocz et al 2011;Gobster et al 2007). In the longstanding weak or peripheral areas, people also recognize factors other than the economic values of the territory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results further illustrate the fact that the rate of population's feeling of belonging to a region offers the potential for forming a vision for development. This vision should reflect regional specificities, including geographically differentiated relationship to the countryside where people live (Chromý, Semian, Kučera 2014;Walker, Ryan 2008;Lokocz et al 2011;Gobster et al 2007). In the longstanding weak or peripheral areas, people also recognize factors other than the economic values of the territory.…”
Section: Resultsmentioning
confidence: 99%
“…Research showed an important role of the level of education, which is assessed by the proportion of university graduates (Chromý, Semian, Kučera 2014). Population with higher education has a deeper relationship to regional identity.…”
Section: Landscape Typementioning
confidence: 99%
“…The results suggest that students most frequently associate the Bohemian Paradise with castles (Trosky, Kost, Valdštejn), the town of Turnov, and the Prachov Rocks. According to Chromý et al (2014), who examined the main symbols of the Bohemian Paradise from the perspective of adult respondents, Trosky and rock formations are pan-regional symbols. When identifying the meanings expressed by the most frequently used adjectives (whether from the perspective of textbook authors or the students themselves), we drew inspiration from Young (1999).…”
Section: Discussionmentioning
confidence: 99%
“…The place most commonly recognized by students is Trosky. Chromý et al (2014) state that it is likely the most depicted symbol of the Bohemian Paradise. The results suggest that there is a significant relationship between students' knowledge of significant places in the Bohemian Paradise and how often they spend time in nature.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the northeastern part and the peripheral parts of the geopark are relatively little-visited [32]. The fact that there are several definitions of the Bohemian Paradise area does not help to improve the situation: on the one hand, it is its historical (or regional identity) delimitation (which is neither clearly defined nor perceived) [43,44], the delimitation of the Protected Landscape Area (with an area of only 181 km 2 ) [45], the delimitation of the geopark (with an area of 833 km 2 ) [37], and delimitation of the tourist area Bohemian Paradise (with an area of 1091 km 2 ) [46]. On the other hand, its strong point is the diversity of the offer of various tourist attractions, where in addition to natural and cultural-historical beauty, there are many opportunities for sports, swimming, socializing, cultural events, etc.…”
Section: Regionmentioning
confidence: 99%